The Phenomenon of Sleeping in Sand Based On Culture In Elderly With Osteoarthritis - Hidayat, Syaifurrahman; Hannan, Mujib; Suprayitno, Emdat; Soares, Domingos; Puji Hastuti, Apriyani; Indriyani, Ratna; Wardita, Yulia; Maria Fernandes Amaral, Manuela (JKG (JURNAL KEPERAWATAN GLOBAL), 2023)
Background: Pain in the elderly with osteoarthritis requires alternative therapy to fulfill their comfort. The purpose of this study was to explore the culture of sleeping on the sand among the coastal elderly with osteoarthritis pain.   Methods: This research method used a qualitative research approach with phenomenological research design and data collection techniques using in-depth interviews, participant observation, and documentation. The time of the research is from April to May 2023, located in Legung Village, Batang-Batang District, Sumenep Regency. The technique was judgment sampling, with nurses as key informants, the elderly as main informants, and traditional and community leaders as supporting informants, so the informants in this study were 18 participants. Data analysis uses athematic analysis based on values, activities, and artifacts.   Results: 1. Cultural elements in the form of values and ideas in the culture of sleeping on the sand include sleep history, belief in sleeping on the sand, and concepts or values in society. 2. The form of activity can be seen in several sand extraction activities or the implementation procedure of preparing sand to be used as the basic material for bedding. 3. The form of the artifacts is related to the tools and materials used in this case, which are related to sleep culture.   Conclusion: The culture of sleeping on the sand has a comforting effect on older people based on three forms of culture, including ideas and values, activities, and artifacts. The culture of sleeping on the sand can be used as a daily activity to overcome the problem of osteoarthritis in older people. This research can be developed regarding the implementation of culture-based transcultural nursing care.